2005
DOI: 10.1111/j.1532-5415.2005.53259.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Hospice Referral and Families' Perceptions of Services: Are Earlier Hospice Referrals Better?

Abstract: These results indicate that families feel they receive greater benefits from longer lengths of stay in hospice. Future efforts to define an "optimal" length of stay in hospice should consider patients' and families' perceptions of the benefits that hospice offers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 20 publications
1
92
0
Order By: Relevance
“…1 Studies have shown that hospice provides quality care for patients at the end of life, with a high satisfaction rate for patients and families. [2][3][4] Nevertheless, this service is underutilized, and many of those who enroll do not subsequently live long enough to fully benefit from hospice care. 2,[5][6][7] Lack of clinicians' discussion about hospice with the patient and family has been identified as a barrier to hospice use, 8,9 supported by retrospective studies, in which caregivers, asked to recall their conversations with clinicians, frequently report an absence of communication about hospice or treatment options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Studies have shown that hospice provides quality care for patients at the end of life, with a high satisfaction rate for patients and families. [2][3][4] Nevertheless, this service is underutilized, and many of those who enroll do not subsequently live long enough to fully benefit from hospice care. 2,[5][6][7] Lack of clinicians' discussion about hospice with the patient and family has been identified as a barrier to hospice use, 8,9 supported by retrospective studies, in which caregivers, asked to recall their conversations with clinicians, frequently report an absence of communication about hospice or treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Nevertheless, this service is underutilized, and many of those who enroll do not subsequently live long enough to fully benefit from hospice care. 2,[5][6][7] Lack of clinicians' discussion about hospice with the patient and family has been identified as a barrier to hospice use, 8,9 supported by retrospective studies, in which caregivers, asked to recall their conversations with clinicians, frequently report an absence of communication about hospice or treatment options. 4,10,11 Although one small study retrospectively estimated that the majority of persons offered hospice by their clinicians utilized this service, there has been no prospective evaluation of the relationship between hospice discussion and use.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that referral for PCU care may occur too late, possibly in part because of inadequate awareness about palliative services. Similar conclusions have been made in a number of studies addressing barriers to palliative care access [13][14][15] , and programs such as Living Lessons have been set up to increase public awareness of palliative care 16 . Schockett et al found that late referral to end-of-life care, such as to outpatient hospice in the United States, was positively associated with lower patient and family satisfaction with care 14 .…”
Section: Discussionmentioning
confidence: 64%
“…A number of U.S. studies looking at outpatient hospice utilization have examined the duration of end-of-life care, finding that the median generally ranges between 3 weeks and 1 month 13,15,[17][18][19] . In a Canadian study from Edmonton, Alberta, Jenkins et al retrospectively examined characteristics of an inpatient PCU with an anticipated LOS of 2 months and reported that, in a sample of 106, the median length of stay was 21 days, ranging between 0 and more than 200 days 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The short length of stay is significant since bereaved families commonly report that more time in hospice would have been beneficial. 5 Medicare has two requirements for hospice eligibility: 1) the patient must understand that his/her illness is life limiting and be willing to forego curative therapy and 2) two physicians must declare that the patient has 6 months or less to live. Hospice agencies often rely on NHPCO published worksheets (designed to identify patients with a prognosis of less than 6 months) to assist in determining if a patient meets the Medicare requirements.…”
Section: Introductionmentioning
confidence: 99%